2023
DOI: 10.3390/ma16072564
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of Storage Stability and Aging Resistance of Slightly SBS-Modified Bitumen Binders

Abstract: Slightly SBS-modified bitumen binders have been applied for the asphalt concrete impermeable layer of pumped storage power stations (PSPSs) in China. However, the storage stability and aging resistance of slightly SBS-modified bitumen are big concerns. In this study, three different types of slightly SBS-modified bitumen binders were evaluated by using a commonly used virgin bitumen and a normal SBS polymer-modified bitumen as references. All of the bitumen binders were subjected to short-term and long-term ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…After numerous trial and error tests in the laboratory, our research team decided that the mixing conditions and procedure used for mixing STP and NA must be the same as those used for mixing IPA1w and NA. This decision was taken after analyzing the storage stability of IPABs according to ASTM-D7173 [37], and the procedure described in a previous study was also followed [38]. Hence, the results demonstrated that the IPABs showed good storage stability after mixing IPA1w and NA following the same procedure as was used for mixing STP and NA.…”
Section: Preparation Of Ipa1w-modified Bitumen (Ipab)mentioning
confidence: 99%
“…After numerous trial and error tests in the laboratory, our research team decided that the mixing conditions and procedure used for mixing STP and NA must be the same as those used for mixing IPA1w and NA. This decision was taken after analyzing the storage stability of IPABs according to ASTM-D7173 [37], and the procedure described in a previous study was also followed [38]. Hence, the results demonstrated that the IPABs showed good storage stability after mixing IPA1w and NA following the same procedure as was used for mixing STP and NA.…”
Section: Preparation Of Ipa1w-modified Bitumen (Ipab)mentioning
confidence: 99%
“…Xu et al [ 25 ] studied the aging resistance of polyether-type polyurethane concrete (PPC), showing that PPC has good aging resistance, and its road performance after aging is better than SBS-modified asphalt mixtures that are not aged. Yu et al [ 26 ] confirmed that highly SBS-modified asphalt has better aging resistance compared to slightly SBS-modified asphalt. Babu et al [ 27 ] enhanced the aging resistance of VG30 asphalt binder by adding Sasobit (warm mix additive) and hydrated lime.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in this area has paved the way for the development of high-quality, long-lasting asphalt materials with improved workability and resistance to factors such as moisture and fatigue, making them integral to the construction and maintenance of modern infrastructure [31,31]. Furthermore, in recent studies [32], significant advancements have been made in understanding the effects of weather aging on modified asphalt with rubber-polyethylene composites and the investigation of storage stability and rheological properties of environmentally friendly devulcanized rubber modified asphalt, respectively. These findings provide valuable insights into the durability and performance of modified asphalt materials under various conditions.…”
Section: Introductionmentioning
confidence: 99%